#### Answer

13

#### Work Step by Step

We are given that $f(x)=x^{2}+4$, $g(x)=2x+3$, and $h(x)=x-5$.
We are asked to find $(f∘g)(0)$. We know that $(f∘g)(x)=f(g(x))$.
Therefore, $(f∘g)(0)=f(g(0))=f(2(0)+3)=f(0+3)=f(3)=3^{2}+4=9+4=13$.

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

13

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.